Importancia de la Agricultura Limpia para la producción de alimentos inocuos”. - Moran Herrera, Melissa Marianela (2020)
This research deals with the importance of clean agriculture based on good agricultural practices for obtaining healthy products that do not generate negative changes in the health of the consumer. Clean agriculture is considered a form of agricultural production that includes organic or ecological agriculture that generates a positive change in the soils that for many years have been poisoned by farmers with chemical products that also cause an effect on the environment. In this research, according to OMS, the consumption of safe food promotes a better quality of life for consumers and producers. In several provinces of Ecuador, organic production is promoted by groups and communities of farmers who made the decision to turn to conventional agriculture, such as the province of Manabí, it can be said that clean agriculture is quite widespread in the country. Worldwide, there is also a large increase in the area of organic agriculture, with more than 100 countries practicing it, as it generates a great benefit to counteract diseases that are caused by food. It is also important to note that organic products have a high cost because they are chemical-free. That is why clean agricultural production is important.